2016
DOI: 10.3126/stcj.v2i1.14799
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Quality Evaluation of Mayonnaise and its Effect on Storage Stability

Abstract: This study aimed to evaluate the addition of skim milk powder to replace egg yolk in preparation of mayonnaise. Egg yolk was pasteurized at 150ºF (65.6ºC) about 1 minute for its safety. Mayonnaise was prepared from sunflower oil with the level varied from 65-75% and egg yolk from 9-15%. Mayonnaise made from 70% oil and 12% egg yolk was found to be best. Then skim milk powder (SMP) was added to replace 12% egg yolk in the ratios 0:100, 25:75, 50:50, 75:25 and 100:0 other constituents remaining constant. Sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Protein levels increased in the control treatment were lower than other treatments (2.02%) and the highest protein levels were observed in the treatment containing 9% protein (5.27%). Eggs contain approximately 70% water, 12.5% protein, 12% fat, and 11.5% ash (Pradhananga & Adhikari, 2015). In this study, clover protein was first dissolved in water so that it has 70% moisture like eggs, then it was replaced with eggs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein levels increased in the control treatment were lower than other treatments (2.02%) and the highest protein levels were observed in the treatment containing 9% protein (5.27%). Eggs contain approximately 70% water, 12.5% protein, 12% fat, and 11.5% ash (Pradhananga & Adhikari, 2015). In this study, clover protein was first dissolved in water so that it has 70% moisture like eggs, then it was replaced with eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Eggs are an important ingredient in the production of mayonnaise due to their nutritional and functional roles, including emulsification, foaming, and stability, and constitute the dominant structure in the continuous phase (Ali and El Said, 2020). However, the health problems associated with the use of eggs is increasing due to their high cholesterol content (Karshenas et al., 2018; Pradhananga and Adhikari, 2015). In general, there is a close relationship between high cholesterol and the incidence of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The acid value obtained was observed to increase during storage. This increase could be mainly attributed to hydrolytic and oxidative enzymes from eggs [40,41] and acidtolerant microorganisms in the aqueous mayonnaise phase [40]. Except for sample S4, there was no significant difference (p < 0.05) between the sample at the 28th day of storage.…”
Section: Oxidative Stabilitymentioning
confidence: 86%
“…The gradual increase in the peroxide values during storage indicated the rancidity of mayonnaise samples. Peroxide values less than 10 indicated that both enriched and simple mayonnaise samples are considered safe in refrigerated conditions [41].…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…Sensory evaluation was carried out after the first week of production. According to Pradhananga et al (2015) [ 25 ], mayonnaise was served with bread to twelve trained panelists for an evaluation through a 9-point hedonic scale (9 = extremely like, 1 = extremely dislike). The median of the judges’ scores given to colour, odour, texture, taste and overall acceptability was calculated.…”
Section: Methodsmentioning
confidence: 99%